(untitled) (LINGUISTIK TERAPAN, 2022)
This study deals with Directive Illocutionary Act of male and female English Teacher in SMP Ad-Durrah Medan. The objectives of this study is to describe the realization of directive illocutionary act of male and female English teachers at SMP Ad-Durrah Medan. This study applied qualitative descriptive method. The techniques for collecting data are through applying observation by taking eight meetings for male and female English teachers to get realization of directive illocutionary act by male and female English. The results of this study found that realization of directive illocutionary act realized from the collaborative, competitive, conflictive , and convivial, where one of the realization was showed that the teacher makes a group discussion for doing the task and the teachers help the students by making a discussion for each student, making a collaboration for their task related to the content of their lesson and presenting the discussion in the class.